Prospective analysis of the association of ambulatory blood pressure characteristics with incident chronic kidney disease. Issue 9 (September 2015) - McMullan, Ciaran J.; Hickson, DeMarc A.; Taylor, Herman A.; Forman, John P.
<x xml:space="preserve">Abstract</x> Objective: Ambulatory blood pressure measurement allows quantification of diurnal changes in blood pressure. While decreased nocturnal blood pressure dipping and elevated morning blood pressure surge are associated with an increased risk of cardiovascular events, the utility of ambulatory blood pressure measurements to predict renal events is unclear. African Americans, in addition to having an increased risk of chronic kidney disease (CKD), also have an increased prevalence of hypertension. Thus, we selected an African American population to study the association of ambulatory blood pressure parameters with incidence of CKD. Methods: Prospective cohort study of 603 participants with normal renal function enrolled in the Jackson Heart Study who underwent baseline 24-h ambulatory blood pressure monitoring between 2000 and 2004, with median follow-up of 8.1 years. We analyzed the association of nocturnal dipping and morning surge with both incident CKD [estimated glomerular filtration rate (eGFR) <60 ml/min per 1.73 m2] and annual rate of eGFR decline. In additional analyses, we examined the relation of nocturnal, daytime, white-coat, and masked hypertension with CKD incidence. Results: We found that 10% higher nocturnal dipping was significantly associated with a decreased risk of incident CKD [odds ratio (OR) 0.55, 95% confidence interval (CI) 0.32–0.96] and a 0.4 ml/min per 1.73 m2 slower annual decline in eGFR. Morning surge was not associated with the incidence of CKD. Additional analyses revealed that isolated nocturnal hypertension and mean asleep SBP were associated with a nonsignificantly higher risk of CKD (OR 2.34, 95% CI 0.90–6.08) and (OR 1.31, 95% CI 0.99–1.72), respectively, in fully adjusted models. Conclusions: Loss of nocturnal blood pressure dipping, but not morning blood pressure surge, may promote the decline in GFR and increase the risk for development of CKD in high-risk individuals.